Uji Kualitas Akustika Masjid Gedhe Mataram di Kotagede Yogyakarta Terhadap Konstruksi Bangunan Masjid - Muhammad Badru Zaman; Tubagus Mulkan Azima (Institut Teknologi Garut, 2022)
The Gedhe Mataram Mosque is the oldest mosque in the city of Yogyakarta which is south of Pasar Kotagede, the Gedhe Mataram Mosque became the main mosque during the Mataram Kingdom and has a unique architectural style, namely with a blend of Hindu-Buddhist, Javanese and Islamic architecture. Until now, the Gedhe Mataram Mosque still maintains its architectural style because it is a historical heritage. The use of structures and materials in the interior of the mosque which is more dominant using natural materials, one of which is the use of wood, with the more dominant use of natural materials is an attraction to study whether the mosque in terms of acoustics meets the applicable standards or not. The research method was carried out by field observation, literature study, and testing using the CATT application. Field observation aims to collect physical data on the research object (Gedhe Mataram Mosque). Literature study aims to collect data about the object of research, and theories of acoustics in mosque buildings. Testing with CATT software aims to determine the initial quality of the mosque building, and the quality of the acoustics resulting from the design recommendations. The existing results obtained by simulating using CATT have an excess of reverberation time. The reverberation level of the acoustic standard for places of worship is 0.7 – 1.1 while the Gedhe Mataram mosque has a hum reaching 1.4 and the form of recommendation that we recommend so that the acoustic reverberation time is in accordance with the standards is by adding a ceiling layer to the interior of the Gedhe Mataram mosque, with an added layer the ceiling of the reverberation time is 0.7 – 0.9 so that it is in accordance with the applicable acoustic standards.